Analisis Kualitas Formula Pupuk Organik Pelet dari Eceng Gondok dan Tandan Kosong Kelapa Sawit (Quality Analysis of Organic Fertilizer Pellets Formula from Water Hyacinth and Oil Palm Empty Fruit Bunch) - I Dewa Gede Putra Prabawa; Nurmilatina Nurmilatina (Kementerian Perindustrian, 2017)
The objective of this research was to analyse organic fertilizer pellets from water hyacinth and oil palm empty fruit bunch (OPEFB) that have not been widely used in South Kalimantan. The variable of the research was the ratio of water hyacinth and OPEFB: 25%:75%, 50%:50%, and 75%:25%. The fertilizer was produced by heating the materials at 350oC, and then composting the materials using effective microorgnism 4 (EM4), and then mold into pellet shape. The results showed that the drying, heating, and composting process could increase nitrogen and phosphor content. Nitrogen in water hyacinth increased from 0.06% to 2.18%, while its increased from 0.18% to 2.49% in OPEFB. Phosphor in water hyacinth increased from 3.42% to 6.89%, while its increased from 1.95% to 4.70% in OPEFB. The quality of organic fertilizer pellet was evaluated according to Permentan No.70-2011. The result showed that the content of C-organic, macro nutrients, micro nutrients, heavy metals, Escherichia coli, Salmonella sp., moisture content, pH, and residue met the requirements. The organic fertilizer contained the highest nutrient made from 50 % water hyacinth and 50% OPEFB.Keywords: organic fertilizer pellets, oil palm empty fruit bunch, water hyacinth